Phenotypic and Genotypic Antibiotic Resistance Patterns in Helicobacter pylori Strains From Ethnically Diverse Population in México - Camorlinga-Ponce, Margarita; Gómez-Delgado, Alejandro; Aguilar-Zamora, Emmanuel; Torres, Roberto C.; Giono-Cerezo, Silvia; Escobar-Ogaz, Antonio; Torres, Javier (Frontiers in Cellular and Infection Microbiology, 2021)
Helicobacter pylori strains carry a range of mutations in genes that confer antimicrobial resistance and restrict the available options to treat the infection. Latin America is a region that conserve a large number of indigenous communities relatively isolated that practice a traditional medicine without consumption of drugs. We hypothesized that rates of antibiotic resistance are lower in these communities. Recent progress in whole-genome sequencing has allowed the study of drug susceptibility by searching for the known mutations associated with antibiotic resistance. The aim of this work was to study trends of antibiotic resistance over a 20-year period in Mexican H. pylori strains and to compare susceptibility between strains from Mexican mestizos and from indigenous population; we also aimed to learn the prevalence of mutational patterns in genes gyrA, gyrB, rdxA, frxA, rpsU, omp11, dppA, and 23S rRNA and its association with phenotypic tests. Resistance to clarithromycin, metronidazole, amoxicillin and levofloxacin was determined in167 H. pylori isolates by E-test, and the occurrence of mutational patterns in specific genes was determined by whole genome sequencing (WGS). The trend of resistance over 20 years in mestizo isolates showed significant resistant increase for clarithromycin and levofloxacin to frequencies that banned its clinical use. Resistance in H. pylori isolates of native communities was lower for all antibiotics tested. Phenotypic resistance showed good to moderate correlation with genotypic tests. Genetic methods for characterizing antibiotic resistance require further validation in each population.